The social use of Internet communication technology as a model: a theoretical approach. - ABDALI, Ahmed (Social Sciences Journal)
The "social use of communication technology" constitutes a distinct field of knowledge on its own, with a theoretical and methodological dimension that is mainly concerned with describing the nature of the relationship between the "human" user and the new communication tool, a concept that corresponds to the concept of "exposure" to traditional media. Research related to this phenomenon is usually interested in analyzing it conceptually by identifying the general and specific characteristics, characteristics and features of this concept, and trying to extract the social and cultural meaning from the technical data, as well as setting general frameworks for the directions of research in it, and finally analyzing the overall framework in which the process takes place, with the aim of reaching insights about it immediately. The outcome, which is what this paper seeks to detail and explain. According to Catherine Distler, is not in the technical appearance of the machine, but rather in the rules of its use and in the will of the actors to manage a joint project, that is, our task - as you say - is to search whether there is a side to this The technological facilities that we possess, a culture that understands the rules of its use, and a will capable of controlling the management of this technology